THE INFLUENCE OF COMPETENCE AND PROFESSIONAL ETHICS OF AUDITORS ON AUDIT QUALITY AT THE ADMINISTRATIVE AND FINANCIAL COURT (TRIBUNAL DE CONTAS TIMOR-LESTE) - Guterres, Alexandre de sousa; Araujo, Delia Iria Magno de; Ximenes, Elias; Godinho , Justina Gilberta (PT. Altin Riset Publishing, 2024)
This study aimed to test and analyze the impact of Auditor Competence (X1) and Auditor Professional Ethics (X2) on Audit Quality (Y) at the Tribunal de Contas Timor-Leste. The research questions focused on determining the extent to which competence (X1) and professional ethics (X2) influence audit quality (Y). The population of the study consisted of all 50 staff members of the Tribunal de Contas, with data collected using a census method through questionnaires. Multiple linear regression analysis, T-tests, and SPSS version 21 were used for statistical analysis. The multiple linear regression equation obtained was Y = -2.006 + 0.536 + 0.321 + e, with a determination coefficient (R²) of 0.329, indicating that 32.9% of the variance in audit quality was explained by the two independent variables, while the remaining 67.1% was influenced by other factors not examined. The T-test results showed that Auditor Competence (X1) had a T-statistic value of 2.429, which was greater than the T-table value of 1.677, with a significance level of 0.019, meaning that it had a positive but insignificant effect on audit quality. On the other hand, Auditor Professional Ethics (X2) had a T-statistic value of 2.930, exceeding the T-table value of 1.677, with a significance level of 0.003, indicating a positive and significant effect on audit quality. Therefore, while competence was not a major determinant, professional ethics significantly contributed to audit quality at the Tribunal de Contas.